Reprimo G>C and P53R2 C>G 4696 single nucleotide polymorphisms and colorectal cancer: A case-control disease-association study. - William D Beasley (2008)
This thesis presents a case-control disease association research project examining association between single nucleotide polymorphisms (SNPs) of the P53R2 and Reprimo genes and colorectal cancer (CRC). Identifying the genetic risk factors may help to reduce the incidence of CRC by allowing identification of individuals at increased CRC risk through genetic screening. Individuals identified as having increased CRC risk could then have tailored management aiming to reduce their risk and detect CRC at an early, potentially curable stage. P53R2 and Reprimo are both involved in cell cycle control and DNA repair. P53R2 supplies deoxyribonucleotides for repair of damaged DNA and Reprimo is involved in cell cycle arrest in response to genotoxic stress, allowing DNA repair to take place or for apoptosis. Both genes are induced by the tumour suppressor gene TP53. Dysfunction of P53R2 or Reprimo may lead to errors in DNA repair or cell cycle arrest, mechanisms that are recognised in carcinogenesis. SNPs are known to be able to alter gene function and it is thought that SNPs may account for some of the molecular pathology involved in common complex diseases such as cancer. Two SNPs were studied, P53R2 C>G 4696 and Reprimo G>C 842, using a case control method. Cases with histologically proven CRC were compared with two control populations; young, healthy individuals and individuals with diverticular disease (DD). DNA was obtained from buccal cell biopsies and the populations genotyped using an allele specific polymerase chain reaction (PCR) or polymerase chain reaction/restriction fragment length polymorphism (PCR/RFLP) methods. Tests for Hardy-Weinberg equilibrium (HWE) and allelic- and genotype-disease association were performed using an on line SNP-disease association calculator. An association between the Reprimo G>C 842 C allele and CRC was detected on heterozygous and allele positivity testing when using the young, healthy population as a control. However, this association is likely to be a false positive result confounding factors and was not replicated when using the matched DD population. The DD population was found to deviate from HWE with respect to Reprimo G>C 824 and therefore a disease association may exist. Otherwise no associations between the study SNPs and CRC were detected.